2011
DOI: 10.3928/02793695-20110802-01
|View full text |Cite
|
Sign up to set email alerts
|

Another Face of Health Care Disparity: Stigma of Mental Illness

Abstract: In many everyday situations, individuals with mental illness face stigma that leads to discrimination. A growing body of evidence suggests that those with mental illness experience disparities in health care and that their medical needs are often overlooked. The purpose of this article is to increase awareness to this problem. Fictional vignettes in which individuals with mental illness seek medical care are presented, followed by discussion on the role discrimination may play in the level of care these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Participants in this study described the experience of stigmatization and discrimination by hospital personnel as a result both of their mental health and/or addictions challenges, and their repeated visits. Evidence of perceived stigmatization and stereotyping of patients with mental illness by health care providers is growing (Clarke et al 2007;Pope 2011;Skosireva et al 2014). While previous inquiry into the ED experiences of frequent users revealed perceived ageism (Olsson and Hansagi 2001), racism (Nairn et al 2004), sexism, and discrimination based on socioeconomic status, the experience of discrimination based specifically on mental health status and substance use has not been previously exposed for this subpopulation.…”
Section: Discussionmentioning
confidence: 94%
“…Participants in this study described the experience of stigmatization and discrimination by hospital personnel as a result both of their mental health and/or addictions challenges, and their repeated visits. Evidence of perceived stigmatization and stereotyping of patients with mental illness by health care providers is growing (Clarke et al 2007;Pope 2011;Skosireva et al 2014). While previous inquiry into the ED experiences of frequent users revealed perceived ageism (Olsson and Hansagi 2001), racism (Nairn et al 2004), sexism, and discrimination based on socioeconomic status, the experience of discrimination based specifically on mental health status and substance use has not been previously exposed for this subpopulation.…”
Section: Discussionmentioning
confidence: 94%
“…Health professionals, including nurses and medical staff, in the acute medical care setting such as emergency departments, medical-surgical wards, intensive care units and general-medical wards are therefore in regular contact with patients who experience mental illness as a co-morbidity to a physical condition. Some literature suggests that health professionals in these “non-mental health” settings find the complex care of these patients challenging and consequently the patient’s experience of care can be poor [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous studies [ 17 19 , 21 , 22 ]. In fact, the neglect of physical well-being in patients with severe mental illnesses, including schizophrenia, is often attributable to an egregious disparity in health [ 12 , 13 ]. Nasrallah et al reported a high proportion of under-diagnosis and under-treatment of hypertension, dyslipidemia and diabetes in schizophrenia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%